Authoritarianism in an age of democratization - Brownlee, Jason 1974- (Cambridge Univ. Press, 2007)
The political origins of durable authoritarianism -- The inception of ruling parties -- Institutional legacies and coalitional tensions -- Ruling parties and regime persistence : Egypt and Malaysia during the third wave -- Elite defections and electoral defeat : Iran during the third wave -- Confrontation and democratization : the Philippines during the third wave -- Conclusions